Bovine serum albumin-imprinted magnetic poly(2-pyrrolidone) microparticles for protein recognition - Dencheva, Nadya Vasileva (2020)
This study reports on the synthesis and adsorption properties of molecularly imprinted porous magnetic microparticles (MIP) based on the biodegradable and sustainable poly(2-pyrrolidone) (PPD or PA4). These new PPD MIP materials were obtained via activated anionic ring-opening polymerization of 2-pyrroldone carried out at 40 °C, in the presence of iron fillers and bovine serum albumin (BSA) as a template. Neither solvent, nor additional crosslinking or porogen agents were used in the PPD MIP synthesis. Analogously, PPD particles without BSA imprinting (NIP) were also produced. Depending on the microparticles composition, their yields were in the 55–70 wt% range, the average size varying between 8 and 25 μm. After characterization of the surface topography of all samples, their adsorption capacity toward the BSA target was assessed as a function of the adsorption time, protein concentration and pH of the medium. All three PPD MIP samples displayed adsorption capacity toward BSA being up to one order of magnitude higher as compared to other BSA-imprinted polymer systems. It was found that the rebinding of BSA on MIP is best described by the Langmuir isotherm, whereas for rebinding on NIP the Freundlich isotherm was the more adequate model. On this basis, the nature of the adsorption on MIP and NIP was discussed. The adsorption toward two other proteins, namely Ovalbumin and Cytochrome C was also tested. The newly synthesized BSA-imprinted PPD MIP displayed selective adsorption for the BSA target being dependent on the pH values of the medium. The easy recovery of the Fe-containing MIP and the capacity of all MIP samples for multiple sorption/desorption cycles was demonstrated.